(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
We live in a persecutory civilization. For two-and-a-half millennia persecution has formed the model by which societies operate. This does not mean that we are the only persecutory civilization. It does not mean that our societies engage in permanent persecutions or that they have not undergone a civilizing process. But for several thousand years the act of persecution has formed a constant in our civilization; it is endemic to society; and the persecuted leader such as Socrates or Jesus has constituted an ideal type in the West. They established the victim as hero as a model of behaviour, followed by authorities such as Origen and Irenaeus. Persecution is usually contrasted with tolerance; it is also opposed to religious freedom; but the actual structure of persecution — its sociology — has only been examined on a handful of occasions. It is time to define it.